TRENDS IN THE DEVELOPMENT OF THE PROFESSIONAL PRE-HIGHER EDUCATION IN THE MODERN CONDITIONS - Kurok, Roman (Professional Pedagogics, 2021)
The relevance of the study is predetermined by the need to define the place of professional pre-higher education in the domestic educational system and the prospects for the development of this newly formed link of professional education. Aim: to outline the main directions of development of professional pre-higher education in the modern conditions of reforming the educational activity in Ukraine. Methods: theoretical analysis of scientific sources – to determine the level of research of the problem; comparison – in order to study scientific approaches to solving the problem. Results: It is proved that today the state of training applicants of professional education does not fully meet the modern needs of the labor market. The main factors that negatively affect the state of training these specialists were identified, namely: the long process of forming the system of professional pre-higher education and structural changes in the activities of the educational institutions of such type; incompleted legislative and legal regulation of this educational level; insufficient funding of the sphere; imperfect mechanism of forming the state order, which does not fully reflect the needs of the labor market; insufficient participation of employers in forming the content of education, solving problems of professional pre-higher education; insufficient personnel potential and imperfect system of professional development and internship of pedagogical staff etc. Conclusions: the scientific article outlines the main directions of developing professional pre-higher education: completing the process of its legal framework forming; standardization of training applicants of the educational and professional degree of “junior bachelor”; consolidating the principles of student-oriented learning in the educational process; expanding the network of institutions with modern training and production infrastructure and forming the single system of professional education, which would combine professional-technical and professional pre-higher education; implementing new decentralized model of management and financing of the sphere; improving the quality of pedagogical staff who train applicants of education on this level.